2009
DOI: 10.1371/journal.pone.0008242
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Stimulates Vasodilatory and Metabolic Pathways in Cultured Human Endothelial Cells

Abstract: Vascular effects of estradiol are being investigated because there are controversies among clinical and experimental studies. DNA microarrays were used to investigate global gene expression patterns in cultured human umbilical vein endothelial cells (HUVEC) exposed to 1 nmol/L estradiol for 24 hours. When compared to control, 187 genes were identified as differentially expressed with 1.9-fold change threshold. Supervised principal component analysis and hierarchical cluster analysis revealed the differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…The absence of GPER agonist effects on genomic actions is in accordance to previous reports in which GPER receptors are described to mediate acute cardiovascular effects in response to estradiol (Li et al, 2012). These effects of estradiol in HUAEC were different from that previously published in HUVEC (Holden et al, 2003;Monsalve et al, 2007;Sobrino et al, 2009). In spite of HUVEC are often used to study endothelial mechanisms, experiments were developed in HUAEC in an attempt to determine if those genetic differences could alter the response to estradiol and to atherogenic compounds like oxLDL.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The absence of GPER agonist effects on genomic actions is in accordance to previous reports in which GPER receptors are described to mediate acute cardiovascular effects in response to estradiol (Li et al, 2012). These effects of estradiol in HUAEC were different from that previously published in HUVEC (Holden et al, 2003;Monsalve et al, 2007;Sobrino et al, 2009). In spite of HUVEC are often used to study endothelial mechanisms, experiments were developed in HUAEC in an attempt to determine if those genetic differences could alter the response to estradiol and to atherogenic compounds like oxLDL.…”
Section: Discussionsupporting
confidence: 77%
“…Despite their common developmental origins, venous and arterial endothelial cells are not identical, differing widely in morphology and function. (Chi et al, 2003;Sobrino et al, 2009;dela Paz and D'Amore, 2009). Moreover, in the case of endothelial cells cultured from umbilical cord, it must take into account that in the umbilical circulation, the vein carries the oxygenated blood while the arteries carry the deoxygenated blood.…”
Section: Introductionmentioning
confidence: 99%
“…In ovine fetal PAEC after exposure to estradiol, both COX-1 mRNA and protein expressions were up-regulated (Jun et al, 1998), whereas in HUVEC estradiol only induces COX-2 expression protein (Akarasereenont et al, 2000). Genome-wide analysis performed in HUVEC exposed to estradiol for 24 hours demonstrated that COX-1 was among the 5 % of proteins which expression was changed more than 1.5 fold-times compared to controls, data that was verified by western blot analysis (Sobrino et al, 2009). Prostacyclin increased levels after vessel stimulation with estradiol have been mainly associated with enhanced expression of COX-1.…”
Section: Delayed (Genomic) Effects Of Estrogens On Prostanoids Vasculmentioning
confidence: 63%
“…In the cardiovascular system, ER and ER have been identified by different techniques in the endothelium, smooth muscle cells and adventitia and on adrenergic nerve endings of arteries from various territories and several species, including humans (Karas et al, 1994;Kim-Schulze et al, 1996;Venkov et al, 1996;Register & Adams, 1998). Although it has been reported cultured endothelial cells do not express ER (Toth et al, 2008), other investigators have demonstrated the presence of both ER and ER mRNA in endothelium (Wagner et al, 2001) and data from our group demonstrate the protein expression of both ER and ER in HUVEC (Sobrino et al, 2009;Sobrino et al, 2010). Although the relative significance of both ER subtypes in the vascular actions of estrogens is still under study, data from mice lacking either ER (Pare et al, 2002;Arnal et al, 2010) or ER (Zhu et al, 2002), and also from a non-functional mutation of ER in a male patient (Sudhir et al, 1997), reveal an impaired vascular function.…”
Section: Estrogens Actions On Endotheliummentioning
confidence: 68%
“…Estrogen has been described to positively upregulate the production of endothelium-derived relaxing factors (EDRF), such as PGI 2 (Sobrino et al, 2009;Sobrino et al, 2010) and the endothelium-derived hyperpolarizing factors (EDHF) (Golding & Kepler, 2001), both of which are important mediators of vascular relaxation in resistance-sized arteries. Concomitantly, a modulating role of estrogen on constrictor factors (EDCF) is observed.…”
Section: Vascular Aging In Females: Effects Of Estrogen On Vascular Fmentioning
confidence: 99%